2002
DOI: 10.1101/gr.73702
|View full text |Cite
|
Sign up to set email alerts
|

Genes in a Refined Smith-Magenis Syndrome Critical Deletion Interval on Chromosome 17p11.2 and the Syntenic Region of the Mouse

Abstract: Smith-Magenis syndrome (SMS) is a multiple congenital anomaly/mental retardation syndrome associated with behavioral abnormalities and sleep disturbance. Most patients have the same ∼4 Mb interstitial genomic deletion within chromosome 17p11.2. To investigate the molecular bases of the SMS phenotype, we constructed BAC/PAC contigs covering the SMS common deletion interval and its syntenic region on mouse chromosome 11. Comparative genome analysis reveals the absence of all three ∼200-kb SMS-REP low-copy repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
97
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 76 publications
0
97
0
1
Order By: Relevance
“…4,5 Human chromosome 17 is syntenic to a approximately 34-cM region of mouse chromosome 11, in which 19 genes are conserved in order and orientation. 28,29 Mouse models for SMS and dup(17)(p11.2p11.2) syndromes, Df(11)17 þ and Dp(11)17 þ , heterozygous for either a deletion or a duplication, respectively, encompassing an approximately 3 Mb mouse syntenic region, have been created, while a gene targeting approach was used to create Rai1 þ /À mice (Table 3). 30,31 Studies showed that both the deletion 31,34 and the Rai1 þ /À mice 30 manifested with craniofacial abnormalities, obesity, altered circadian rhythm, seizures, and hypoactivity, with the few viable Rai1 À/À mice exhibiting severe neurological abnormalities, motor dysfunction, overt seizures, and learning deficits (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Human chromosome 17 is syntenic to a approximately 34-cM region of mouse chromosome 11, in which 19 genes are conserved in order and orientation. 28,29 Mouse models for SMS and dup(17)(p11.2p11.2) syndromes, Df(11)17 þ and Dp(11)17 þ , heterozygous for either a deletion or a duplication, respectively, encompassing an approximately 3 Mb mouse syntenic region, have been created, while a gene targeting approach was used to create Rai1 þ /À mice (Table 3). 30,31 Studies showed that both the deletion 31,34 and the Rai1 þ /À mice 30 manifested with craniofacial abnormalities, obesity, altered circadian rhythm, seizures, and hypoactivity, with the few viable Rai1 À/À mice exhibiting severe neurological abnormalities, motor dysfunction, overt seizures, and learning deficits (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The two copies of CMT1A-REP and three SMS-REPs are absent in rodent species (Fig. 6A) (Pentao et al 1992;Chen et al 1997;Probst et al 1999;Bi et al 2002). As an initial segmental duplication event, before the divergence of New World monkeys ∼40-65 Mya, the ∼151-Kb proximal portions of LCR17p, LCR17pA/C, and LCR17pA/D were duplicated and inserted, resulting in the adjacent LCR17pC (Fig.…”
Section: Lcr17pe (mentioning
confidence: 99%
“…Interestingly, Inoue et al (2001) and Bi et al (2002) reported decreased recombination over the ∼1.4-Mb CMT1A and ∼4-Mb SMS genomic regions in proximal 17p, potentially representing the evolutionary remnant of low evolutionary recombination activity. It will be interesting to analyze the recombination activity in other LCR-rich genomic regions.…”
Section: Genome Research 2215mentioning
confidence: 99%
See 1 more Smart Citation
“…Next we undertook systematic sequencing of genes in individual SMS129 beginning with three genes localized to the SMS critical interval 4,6,8 : developmentally regulated GTP binding protein 2 (DRG2), RAS dexamethasone-induced 1 (RASD1) and retinoic acid induced 1 (RAI1). We identified no mutations in either RASD1 or DRG2 but found a deletion of 29 bp in exon 3 of RAI1 on one allele in individual SMS129 (Fig.…”
mentioning
confidence: 99%